The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1516-14392013005000129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooling rate on (ε, α') martensite formation in twinning/transformation-induced plasticity Fe-17Mn-0.06C steel

Abstract: The cooling rate, density of stacking faults, austenite grain size, and temperature strongly influence the γ fcc → ε hcp → α' bcc martensite transformation in austenitic alloys. During cooling, austenitic Fe-Mn steels can partially transform to ε and α' martensites within a restricted chemical composition. Martensite formation will influence the mechanical behavior of the alloy. The microstructure evolution under three cooling rates of a hot-rolled austenitic steel, Fe-17.0Mn-0.06C (wt%), was analyzed by optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 30 publications
0
14
0
2
Order By: Relevance
“…The samples were first etched with nital (10%) and then with Klemm's I etchant [23,24]. For the Scanning electron microscopy (SEM) measurements, the samples were etched with Villela etchant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were first etched with nital (10%) and then with Klemm's I etchant [23,24]. For the Scanning electron microscopy (SEM) measurements, the samples were etched with Villela etchant.…”
Section: Methodsmentioning
confidence: 99%
“…For the quantification of the austenite and the and ␣ martensites, the direct comparison method was used [16], which involves the integration of the most intense peaks of each phase characterized by the (1 1 1), (2 0 0), (2 2 0), and (3 1 1) planes of austenite, the (1 1 0), (2 0 0), (2 1 1), and (2 2 0) planes of ferrite, and the (1 0 0), (0 0 2), (1 0 1), and (1 0 2) planes of martensite. The integration of the intensities was done with support of a graphic software (Origin TM ), following the methodology described by Dafé et al [23].…”
Section: Methodsmentioning
confidence: 99%
“…This indicated that a possible martensitic transformation was also responsible by the deformation , in addition to twinning. The procedure for calculating the SFE has described in detail elsewhere 6 . Saeed-Akbari et al 7 calculated the SFE values for steels containing 10-35%Mn (wt%).…”
Section: Resultsmentioning
confidence: 99%
“…Gutierrez-Urrutia and D. Raabe 25 in their study of FeMnAlC steels, and many other researchers, reported a form of carbides at the grain boundaries in the sediments, the k-carbides (Fe, Mn) 3 AlC. 24,25 SEM images of the second phase are precipitated in the grain boundary (Fe,Mn) 3 AlC phase. This phase is reported in the austenite grain boundaries of FeMnAl steel with high carbon content after hot-rolling, and is deposited after an aging process.…”
Section: -23mentioning
confidence: 87%
“…Stability against the g ® e martensite transformation is usually considered to imply stability against the g ® a' martensite transformation since e martensite laths form as an intermediate phase. 8,24 The Diffraction Pattern is given in Figure 6.…”
Section: -23mentioning
confidence: 99%